A Case Report and Review on Cushing’s Syndrome - Thomas, Anisha; Roy, Raima; Arjun, Akhila S (Indian Journal of Pharmacy Practice)
Cushing’s syndrome is a rare endocrine disorder that comprises a large group of signs and symptoms resulting from chronic exposure to excess cortisol, a hormone that adrenal gland produces and corticosteroids. Most cases of Cushing’s syndrome are due to increased adrenocorticotropic hormone production from a pituitary adenoma, which is referred to as Cushing’s disease. Most of the signs and symptoms are nons-pecific and common in the general population, making a diagnosis often challenging. However, several dermatological manifestations, such as fragile skin, easy bruising and reddish purple striae, are more discriminatory. Because uncontrolled Cushing’s syndrome of any etiology is associated with substantial morbidity, including increased cardiovascular disease and mortality, it is important to make an early diagnosis. Unfortunately, median delays of 2 years to diagnosis have been reported. We report a case of a female paediatric patient who is a known case of idiopathic thrombocytopenic purpura who had multiple dermatological findings, including facial plethora, easy bruising, hirsutism and acne, the latter 2 signs reflecting androgen excess.
Keywords: Cushing’s syndrome; Cortisol; Corticosteroids; Adrenocorticotropic hormone.